Konsep Darurat dalam Hukum Islam - Solikhin, Iin (Al-Manahij: Jurnal Kajian Hukum Islam, 2008)
The important point in Islamic law is justice and punishment. This principal is the reference in deciding an Islamic law. The execution of d{aru>rah in Islamic law is natural because its priorities the ease and avoiding difficulties. D{aru>rah has some meanings. Al-Jas}s}a>s stated as the fear of the damage of soul and body. D{aru>rah is something which is related to the big problems which need ease (mashaqqah).